Heterogeneity within AML with CEBPA mutations; only CEBPA double mutations, but not single CEBPA mutations are associated with favourable prognosis - Pabst, T (Nature Publishing Group, 2009)
CCAAT/enhancer binding protein alpha (CEBPA) mutations in AML are associated with favourable prognosis and are divided into N- and C-terminal mutations. The majority of AML patients have both types of mutations. We assessed the prognostic significance of single (n=7) and double (n=12) CEBPA mutations among 224 AML patients. Double CEBPA mutations conferred a decisively favourable overall (P=0.006) and disease-free survival (P=0.013). However, clinical outcome of patients with single CEBPA mutations was not different from CEBPA wild-type patients. In a multivariable analysis, only double – but not single – CEBPA mutations were identified as independent prognostic factors. These findings indicate heterogeneity within AML patients with CEBPA mutations.